2020
DOI: 10.1007/s00395-019-0767-5
|View full text |Cite
|
Sign up to set email alerts
|

FHL-1 is not involved in pressure overload-induced maladaptive right ventricular remodeling and dysfunction

Abstract: Aims The cytoskeletal signaling protein four and-a-half LIM domains 1 (FHL-1) has recently been identified as a novel key player in pulmonary hypertension as well as in left heart diseases. In this regard, FHL-1 has been implicated in dysregulated hypertrophic signaling in pulmonary arterial smooth muscle cells leading to pulmonary hypertension. In mice, FHL-1-deficiency (FHL-1 −/− ) led to an attenuated hypertrophic signaling associated with a blunted hypertrophic response of the pressure-overloaded left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
(78 reference statements)
2
18
0
Order By: Relevance
“…Prolonged reperfusion causes significant changes in both cardiomyocytes and coronary microcirculation. Following 3.5 h of reperfusion, myocardium displays a diffused necrosis band blended with hyper-contracted sarcomeres 18 . Post-ischemic myocardium exhibits massive intravascular accumulation of neutrophils.…”
Section: Pathology Of Coronary Microvascular Ecs Damage In MImentioning
confidence: 99%
“…Prolonged reperfusion causes significant changes in both cardiomyocytes and coronary microcirculation. Following 3.5 h of reperfusion, myocardium displays a diffused necrosis band blended with hyper-contracted sarcomeres 18 . Post-ischemic myocardium exhibits massive intravascular accumulation of neutrophils.…”
Section: Pathology Of Coronary Microvascular Ecs Damage In MImentioning
confidence: 99%
“…Quantitative Real-Time Polymerase Chain Reaction (qRT-PCR). Samples were incubated with TRIzol reagent (Invitrogen) to extract total RNA [54]. CRNDE, miR-4262, and ZEB1 cDNA were synthesized using the Allin-One™ cDNA Synthesis Kit (FulenGen, Guangzhou, China) [55].…”
Section: Mitochondrial Membrane Potential (Mmp) Assessmentmentioning
confidence: 99%
“…Previous studies have shown that ER stress and oxidative stress were extremely significant in macrophage polarization and proinflammatory factor secretion [ 58 60 ]. ER stress, oxidative stress, and inflammatory response together make up defense networks of the cells that react to outside stimuli [ 8 , 61 ].…”
Section: Discussionmentioning
confidence: 99%